(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Background: Physical activity guidelines are recognised as an important element of a national approach to promote physical activity. This presentation summarises the approach and process taken to update the Swiss Guidelines, discusses experiences and identifies challenges. Methods: The multistage project involved to: 1) summarise the scientific evidence underpinning the 2020-edition of the World Health Organization (WHO) guidelines; 2) to systematically analyse the existing Swiss guidelines for different target groups and to develop proposals for updates; 3) a participatory process to gain consensus with the main interested groups; 4) to finalise the guidelines. Results: Updated guidelines were adopted for infants, pre-school children, children and young people, adults, older adults, and pregnant and postpartum women, in most cases adopting the WHO guidelines. Children, young people, and adults living with disability, as well as adults and older adults with chronic conditions are specifically addressed in each of the general guidelines, rather than adopting separate guidelines for each of these groups as done by the WHO. Conclusion: The systematic approach in identifying aspects to update, the participatory approach, and a strong scientific consortium with different thematic backgrounds were key strengths in the process. Challenges included the large amount of feedback and finding scientifically sound compromises. The updated versions of the Swiss national guidelines for small children, young people, adults, and women during and after pregnancy provide an excellent basis to further promote physical activity in Switzerland. A next key task is to develop a range of communication tools and materials for different target groups beyond the circle of experts and interested groups, considering available evidence on optimal messaging and best outlet tools and channels. Acknowledgement: The authors declare that the process of updating the Swiss Physical Activity Guidelines was commissioned by the Federal Ofﬁce of Sport (VM ref. 193007630). Keywords: Physical activity, guidelines, recommendations, stakeholder process